Development of an algorithm to protect user communication devices against data leaks - Zadereyko, Alexander; Prokop, Yuliia; Trofymenko, Olena; Loginova, Natalia; Plachinda Оlha (Eastern-European Journal of Enterprise Technologies, 2021)
In order to identify ways used to collect data from user communication devices, an analysis of the interaction between DNS customers and the Internet name domain space has been carried out. It has been established that the communication device’s DNS traffic is logged by the DNS servers of the provider, which poses a threat to the privacy of users. A comprehensive algorithm of protection against the collection of user data, consisting of two modules, has been developed and tested. The first module makes it possible to redirect the communication device’s DNS traffic through DNS proxy servers with a predefined anonymity class based on the proposed multitest. To ensure a smooth and sustainable connection, the module automatically connects to a DNS proxy server that has minimal response time from those available in the compiled list. The second module blocks the acquisition of data collected by the developers of the software installed on the user’s communication device, as well as by specialized Internet services owned by IT companies. The proposed algorithm makes it possible for users to choose their preferred level of privacy when communicating with the Internet space, thereby providing them with a choice of privacy level and, as a result, limiting the possibility of information manipulation over their owners. The DNS traffic of various fixed and mobile communication devices has been audited. The analysis of DNS traffic has enabled to identify and structure the DNS requests responsible for collecting data from users by the Internet services owned by IT companies. The identified DNS queries have been blocked; it has been experimentally confirmed that the performance of the basic and application software on communication devices was not compromised.